Implementasi Perlindungan Hak-Hak Tersangka dan Asas Praduga Tak Bersalah dalam Proses Penyidikan di Polres Konawe Selatan - Hendra Ahmadi; Muh. Asrianto Zainal; Asni Asni (Institut Agama Islam (IAIN) Kendari, 2021)
This study aims to determine the implementation of the suspect’s rights and the principle of presumption of innocence in the investigation process at the Konawe Selatan Police Station. The results of the study indicate that there are still some rights of the suspect that are not fulfilled, such as the right to obtain legal assistance, the right to get a prompt examination, the right not to be tortured. Likewise, the principle of presumption of innocence has also not been implemented properly, as there are still some suspects who are in the investigation stage experiencing psychological torture. The main things that become obstacles, (1) There is still a strong military culture in the police force so harsh treatments are considered as a matter of course, (2) there are still unscrupulous investigators who are obsessed with pursuing the suspect’s confession, (3) lack of knowledge and understanding of the suspect on the rights of a suspect, (4) the suspect lack of knowledge of the principle of the presumption of innocence